2018
DOI: 10.1155/2018/9390140
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Oxidative Stress in the Newborn: From Pathogenesis to Novel Therapeutic Targets

Abstract: Sepsis is at present one of the leading causes of morbidity and mortality in the neonatal population. Together with inflammation, oxidative stress is involved in detrimental pathways activated during neonatal sepsis, eventually leading to organ dysfunction and death. The redox cascade during sepsis is mainly initiated by IL-6 and IL-8 stimulation in newborns and includes multiple noxious processes, as direct cell damage induced by reactive oxygen species, activation of gene expression leading to amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 128 publications
1
41
0
3
Order By: Relevance
“…In the present study, the effects of MG-infection on structural integrity and immune function of chicken BOF were scrutinized. Oxidative stress is increased during many pathogenic infections (34). Similarly, our data also showed that MG-infection induced oxidative stress and significantly reduced antioxidant activities at day 3 and day 7 post-infection.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the effects of MG-infection on structural integrity and immune function of chicken BOF were scrutinized. Oxidative stress is increased during many pathogenic infections (34). Similarly, our data also showed that MG-infection induced oxidative stress and significantly reduced antioxidant activities at day 3 and day 7 post-infection.…”
Section: Discussionsupporting
confidence: 82%
“…ROS and RNS are originated from mitochondria as a consequence of aerobic metabolism and are normally removed from cells by antioxidant enzymes. 6,7 The imbalance between production and clearance of radicals causes oxidative stress. 7 In neonatal sepsis, causative organisms establish pro-oxidant and proinflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Toxins released by the causative organisms cause sequential events including the release of inflammatory mediators and production of reactive oxygen species (ROS) as well as reactive nitrogen species (RNS). 6 The failure of removing ROS and RNS due to the imbalance between their production and antioxidant defense agents is called oxidative stress. 7 Oxidative stress is a redox cascade associated with the damage of DNA and dysfunction of different organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Oxidative stress as a cause of mitochondrial dysfunction appears to be particularly prominent in neonates. [69] In this study, we have demonstrated that eCIRP is su cient to increase cardiomyocyte ROS and mitochondrial superoxide, increase calcium in ux into mitochondria, and promote depolarization of the mitochondria. Furthermore, we have shown that inhibition of the eCIRP/TREM-1 interaction with the M3 peptide ameliorated these effects.…”
Section: Discussionmentioning
confidence: 65%